1990
DOI: 10.1016/s0022-5347(17)39992-5
|View full text |Cite
|
Sign up to set email alerts
|

Radical Extensive Surgery for Renal Cell Carcinoma: Long-Term Results and Prognostic Factors

Abstract: We studied 200 consecutive patients with renal cell carcinoma who underwent radical nephrectomy and extensive lymphadenectomy. Of the patients 25% already had distant metastasis at operation. Higher T stages tended to be associated with positive nodes (p less than 0.01) and distant metastasis (p less than 0.001). However, in patients with stage N0M0V0 tumors we found no statistically significant difference in survival in relationship to the T stage of the disease (5-year survival: stage T1 80%, stage T2 68% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
2
11

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(105 citation statements)
references
References 30 publications
4
88
2
11
Order By: Relevance
“…'s study, eighty-seven cases of chromophobe renal cell carcinoma were investigated. Authors emphasized that the fact that all the 8 dead chromophobe RCC patients had FNG-2, supports this opinion (13)(14)(15)(16)(17). According to our observations, tissue fixing is a misleading factor that complicates the evaluation.…”
Section: Discussionsupporting
confidence: 72%
“…'s study, eighty-seven cases of chromophobe renal cell carcinoma were investigated. Authors emphasized that the fact that all the 8 dead chromophobe RCC patients had FNG-2, supports this opinion (13)(14)(15)(16)(17). According to our observations, tissue fixing is a misleading factor that complicates the evaluation.…”
Section: Discussionsupporting
confidence: 72%
“…This rate was similar to that of patients with pT3N0M0 tumors and was significantly higher than the 7% observed for patients with distant metastases. 107 In this study they also found that the number of involved nodes (1 vs 42 nodes) did not correlate with outcome. In later survival studies nodal involvement (N0 vs N1-3) was found to confer an unfavorable prognosis and this was shown to retain significance along with patient age and pT category, on multivariate analysis.…”
Section: Lymph Node Metastasesmentioning
confidence: 49%
“…114,115 It has also been shown that although lymph node dissection is associated with increased survival in the short term-with an increased median survival of 5 months, this advantage was lost over a 5-year follow-up period. 115 Lymph node metastases have been reported in 9-27% of cases of RCC, 107 however, evaluation of the role of lymph node dissection in the management of patients with RCC is hampered by the relative scarcity of patients with lymph node metastases in the absence of extranodal tumor spread. This is highlighted by autopsy studies on patients with clinically unrecognized disease, where only 4.2% of cases were found to have metastases confined to lymph nodes.…”
Section: Lymph Node Metastasesmentioning
confidence: 99%
“…The reported survival rate of patients with exclusive NM demonstrates great variability, and ranges from 5 to 40%. [3][4][5][6][7][8][9] Even after consideration of staging biases, these survival rates are in clear contrast with survival estimates from patients with localized disease (T 1-3 N 0 M 0 ), where 5-year survival exceeds 85%. Therefore, patients with NM have clearly more aggressive disease than even the worst variant of localized disease.…”
mentioning
confidence: 91%